2018
DOI: 10.1021/acschembio.7b01042
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-Directed Chemistry of AMPA Receptors Confers Live-Cell Fluorescent Biosensors

Abstract: AMPA-type glutamate receptors (AMPARs) mediate fast excitatory synaptic transmission in the central nervous system. Dysregulation of AMPAR function is associated with many kinds of neurological, neurodegenerative, and psychiatric disorders. As a result, molecules capable of controlling AMPAR functions are potential therapeutic agents. Fluorescent semisynthetic biosensors have attracted considerable interest for the discovery of ligands selectively acting on target proteins. Given the large protein complex form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…It has been demonstrated that LD and AG chemistries are applicable for visualization of endogenous proteins, 211,215,217,218 biosensor construction, 11,12,[219][220][221] protein-protein interaction analyses, [222][223][224] design of a new type of covalent inhibitor 199 and drug screening in live cell environments. 221 For example, Hamachi, Kiyonaka and coworkers recently demonstrated that fluorophore-labeled AMPA-type glutamate receptors (AMPARs) prepared by LDAI chemistry act as turn-on-type fluorescent biosensors for AMPAR ligands under live cell conditions.…”
Section: •3 Chemical Labeling Using Affinity-guided Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that LD and AG chemistries are applicable for visualization of endogenous proteins, 211,215,217,218 biosensor construction, 11,12,[219][220][221] protein-protein interaction analyses, [222][223][224] design of a new type of covalent inhibitor 199 and drug screening in live cell environments. 221 For example, Hamachi, Kiyonaka and coworkers recently demonstrated that fluorophore-labeled AMPA-type glutamate receptors (AMPARs) prepared by LDAI chemistry act as turn-on-type fluorescent biosensors for AMPAR ligands under live cell conditions.…”
Section: •3 Chemical Labeling Using Affinity-guided Catalystsmentioning
confidence: 99%
“…221 For example, Hamachi, Kiyonaka and coworkers recently demonstrated that fluorophore-labeled AMPA-type glutamate receptors (AMPARs) prepared by LDAI chemistry act as turn-on-type fluorescent biosensors for AMPAR ligands under live cell conditions. 220 These biosensors selectively detect orthosteric ligands for AMPARs. Notably, the dissociation constants of competitive ligands to AMPAR (both agonists and antagonists) were successfully determined in live cells, by which they clearly demonstrated that the agonists-binding properties of AMPARs are largely different between live cell environments and noncellular conditions.…”
Section: •3 Chemical Labeling Using Affinity-guided Catalystsmentioning
confidence: 99%
“…The imidazole carbamate reactive moiety has been extensively used to study the biology of proteins (Figure C), especially membrane bound receptors . During the conjugation reaction, the imidazole acts as a leaving group transferring the label containing alkyl formate to the protein.…”
Section: Reactive Moietymentioning
confidence: 99%
“…It showed superior labeling of the folate receptor on live cells compared to a benzenesulfonate probe. While the kinetics of imidazole carbamate probes have not been further investigated in vitro, imidazole carbamate probes have been successfully employed to investigate the biology of both GABA A and AMPA receptors by live cell labeling. Through the highly selective complexation of the guiding moiety and the delicate reactivity of the imidazole carbamate, it was possible to label the AMPA receptors in cultured neurons, and more impressively, in brain tissue of acute hippocampal slices.…”
Section: Reactive Moietymentioning
confidence: 99%
See 1 more Smart Citation